2020
DOI: 10.3389/fpls.2020.00170
|View full text |Cite
|
Sign up to set email alerts
|

High Density Mapping of Quantitative Trait Loci Conferring Gluten Strength in Canadian Durum Wheat

Abstract: Gluten strength is one of the factors that determine the end-use quality of durum wheat and is an important breeding target for this crop. To characterize the quantitative trait loci (QTL) controlling gluten strength in Canadian durum wheat cultivars, a population of 162 doubled haploid (DH) lines segregating for gluten strength and derived from cv. Pelissier × cv. Strongfield was used in this study. The DH lines, parents, and controls were grown in 3 years and two seeding dates in each year and gluten strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Regarding the stability of GY, Hou et al (2014) showed that TaSus1-7A carrying Hap-1/2 had a higher 1000-grain weight in multiple environments, which indicated the stable expression of the grain weight trait of Hap-1/2 [ 73 ]. Regarding the stability of PC, Ruan et al (2020) conducted a two-year trial with 162 double haploid durum wheat populations and found that the favorable allele of Glu-B3 was stably expressed in all environments tested [ 78 ]. In the present study, wheat cultivars Liangxing 66 and Xinmai 18 contained both stable genes, TaSus1-7A and Glu-B3, which indicates that their PC and GY can be stably expressed under low-input management.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the stability of GY, Hou et al (2014) showed that TaSus1-7A carrying Hap-1/2 had a higher 1000-grain weight in multiple environments, which indicated the stable expression of the grain weight trait of Hap-1/2 [ 73 ]. Regarding the stability of PC, Ruan et al (2020) conducted a two-year trial with 162 double haploid durum wheat populations and found that the favorable allele of Glu-B3 was stably expressed in all environments tested [ 78 ]. In the present study, wheat cultivars Liangxing 66 and Xinmai 18 contained both stable genes, TaSus1-7A and Glu-B3, which indicates that their PC and GY can be stably expressed under low-input management.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of variance (ANOVA) and heritability estimate were performed using the PROC MIXED procedure of SAS 9.3 (SAS Institute, Cary, NC, USA) as described by Ruan et al ( 2020 ). In the mixed model, DH lines (genotypes, G) were considered as fixed effects, while environments (E), genotype × environment (G × E) interactions and replications nested in environments were considered as random effects.…”
Section: Methodsmentioning
confidence: 99%
“…QTL mapping was performed using the genetic map of Pelissier × Strongfield reported by Ruan et al ( 2020 ). The Infinium iSelect Wheat 90K SNP chip was used for genotyping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Calayugan et al, 2020) were detected. In wheat, five QTLs for gluten strength (including QGlu.spa-1A and QGlu.spa-1B.1 on chr 1A and 1B, respectively) were identified (Ruan et al, 2020). Additionally, 16 wheat QTLs for grain Fe, Zn and protein contents, and 1000-kernel weight were identified, encompassing four Fe QTLs (QGFe.iari-2A, QGFe.iari-5A, QGFe.iari-7A and QGFe.iari-7B), five Zn QTLs (QGZn.iari-2A, QGZn.iari-4A, QGZn.iari-5A, QGZn.iari-7A and QGZn.iari-7B), two protein content QTLs (QGpc.iari-2A and QGpc.iari-3A), and five 1000-kernel weight QTLs (QTkw.iari-1A, QTkw.iari-2A, QTkw.iari-2B, QTkw.iari-5B and QTkw.iari-7A) (Krishnappa et al, 2017).…”
Section: Omics Facilitated Crop Improvement For Nutritive Traitsmentioning
confidence: 99%